Arteries and Veins or Bowels and Vessels – On Lexical Fixedness in the Eighteenth-Century Medical Texts - Magdalena Bator; Marta Sylwanowicz (Acta Universitatis Sapientiae: Philologica)
. The proposed paper aims to conduct a corpus-driven examination of the eighteenth-century English vocabulary used in various types of medical texts such as treatises, recipes, regimens, surgical texts, etc It is argued that formulaicity in medical jargon depended on the text type We focus on binomials, defined as “words or phrases belonging to the same grammatical category having some semantic relationship and joined by some syntactic device such as ‘and’ or ‘or’” (Bhatia 1993: 108) Apart from the investigation into the correspondence between the use of binomials and the text type, the analysis involves exploring their frequency, origin, the type of relationship between their components, and the (ir) reversibility of these elements The study delves into the purpose of using binomials in the examined texts and addresses such key questions as: to what extent was the medical language of the eighteenth century formulaic, whether lexico-syntactic patterns of binomials were repeated across particular types of texts, and whether there was any stability in the structure of the phrases The material used for the analysis is the electronic corpus of Late Modern English Medical Texts (LMEMT, Taavitsainen and Hiltunen 2019), containing a representative collection of texts (of over two million words) from a wide range of eighteenth-century medical writings We adopt the typology and methodology used by Kopaczyk (2013), Mollin (2014), and Kopaczyk and Sauer (2017).